2005
DOI: 10.1002/cne.20666
|View full text |Cite
|
Sign up to set email alerts
|

Comparative localization of two serotonin receptors and sensorin in the central nervous system ofAplysia californica

Abstract: Aplysia californica is a powerful model for understanding the cellular and molecular mechanisms underlying modulation of neuronal plasticity and learning. In the central nervous system of Aplysia, serotonin is associated with various behaviors. For example, it induces short-, intermediate-, and long-term synaptic changes in sensory neurons during learning and inhibits the afterdischarge of the bag cells that initiate egg-laying behavior. Little is known about the nature and contribution of serotonin receptors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…As stated above, the pleural sensory neurons serve as mechanoreceptors with a nociceptive role, and thus inhibition with dopamine [or with 5-HT in the small subset of sensory neurons that express endogenous 5-HT 1Apl(a) ; Barbas et al 2005;Dunn et al 2012] would be expected to have a hypoalgesic or analgesic effect on behavior. Interestingly, modulation of nociception in vertebrates appears to function through a conserved general mechanism, namely a reduction in membrane excitability and reduced transmitter release through reduced calcium influx (Cregg et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated above, the pleural sensory neurons serve as mechanoreceptors with a nociceptive role, and thus inhibition with dopamine [or with 5-HT in the small subset of sensory neurons that express endogenous 5-HT 1Apl(a) ; Barbas et al 2005;Dunn et al 2012] would be expected to have a hypoalgesic or analgesic effect on behavior. Interestingly, modulation of nociception in vertebrates appears to function through a conserved general mechanism, namely a reduction in membrane excitability and reduced transmitter release through reduced calcium influx (Cregg et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Similar inhibition (reduction in membrane excitability and synaptic efficacy) is observed with activation of a known 5-HT receptor, the Aplysia 5-HT 1Apl(a) receptor, that can be exogenously expressed (Angers et al 1998;Dunn et al 2012). The 5-HT 1Apl(a) receptor is only endogenously expressed in a very small subset of pleural sensory neurons (Barbas et al 2005;Nagakura et al 2010;Dunn et al 2012). Therefore, we overexpressed the receptor with an eGFP tag [5-HT 1Apl(a) -eGFP] in cultured sensory neurons with nuclear microinjection of pNEX3 vectors containing the tagged receptor (Nagakura et al 2010).…”
Section: Inhibition Of the Isolated Inward Barium Current With Dopamimentioning
confidence: 99%
“…Given that imatinib has been reported to modulate immune cell function and secretion profile, it was surprising to observe that imatinib treatment had no significant impact on plasma concentrations of pro-inflammatory cytokines, IL-β, IL-6, IL-8, and TNF-α, reported to be involved in the orchestration of the inflammatory response [44], [39], [37] at 6 hours post-injury which translates to 5.5 hours after the treatment began. It was also surprising to find that imatinib had no impact on neutrophil infiltration into the injured spinal cord 24 hours after injury.…”
Section: Discussionmentioning
confidence: 99%
“…Using both invertebrates and mammals, recent studies have revealed that endogenous 5-HT modulates plasticity processes, including learning and memory (Meneses, 1999;Barbas et al, 2003Barbas et al, , 2005Schmitt et al, 2006). It has been shown that pharmacological manipulation of 5-HT1-7 receptors or 5-HT re-uptake sites might modulate memory consolidation, which is consistent with the emerging notion that 5-HT plays a key role in memory formation (reviewed by Meneses, 2002;Meneses, 2007).…”
Section: Discussionmentioning
confidence: 53%